Ogled kohezijske vloge slovenskega členka - Skubic, Andrej E. (Slavistična revija, 1999)
Slovenian parts-of-speech theory describes particles primarly according to semantic criteria, not according to the role they play in the clause structureand in proposition. It seems that in relation to the proposition, their roles are mainly twofold: cohesive and modal. These functions are analogous with those of Conjuctive and modal Adjuncts in Halliday's Systemic Functional Grammar.
Keywords: besedne vrste; členek (ling.); slovenščina